A COMPARATIVE ANALYSIS OF SEMITIC AND NON-SEMITIC RELIGIONS: AN OVERVIEW AND COMPARISON: سامی مذاھب اور غیر سامی مذاھب کا مختصر تعارف اور ان کا تقابلی جائزہ - Maria Jaffar (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper provides a concise introduction to Semitic and non-Semitic religions, exploring their fundamental characteristics and distinguishing features. It aims to offer a comparative assessment of Semitic and non-Semitic religions, highlighting their historical contexts, belief systems, practices, and cultural influences. Through a comprehensive analysis, the paper seeks to elucidate the similarities and differences between Semitic and non-Semitic religions, shedding light on their impacts on societies and civilizations. Key areas of examination include theological doctrines, ritualistic practices, sacred texts, and the socio-political dimensions of these religious traditions. The study endeavours to contribute to a deeper understanding of the diverse religious landscape, fostering interfaith dialogue and scholarly inquiry.